Efektivitas Program Surabaya Intelligent Transport System untuk mengatasi kemacetan di kota Surabaya - Subianto, Yohanes Septian; Arimurti Kriswibowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of E-Government is carried out to support the service processes provided to the public. Surabaya City has been a pioneer in the implementation of e-government since 2002. With the issuance of Surabaya Mayor Regulation Number 5 of 2013 concerning Guidelines for the Utilization of Information and Communication Technology in the Implementation of Local Government, the Surabaya Transportation Agency created a system aimed at improving security, reducing congestion, and monitoring traffic by establishing the Surabaya Intelligent Transport System (SITS). The researcher conducted a study on SITS due to the persisting traffic congestion in Surabaya, and the objective of this research is to describe the effectiveness of traffic monitoring through the Surabaya Intelligent Transport System (SITS) in Surabaya. The research method used is qualitative descriptive, utilizing both primary and secondary data. Data collection is carried out through interviews, observations, and documentation. The theory used in this research is the effectiveness theory according to Campbell J. P, which has 5 indicators: program success, target success, satisfaction with the program, input and output levels, and overall goal achievement. The results of this research show that the implementation of SITS in the production indicators is quite optimal, the efficiency indicators of SITS are efficient in alleviating congestion, the satisfaction indicators of SITS meet the criteria, the adaptation indicators are quite good but lack socialization, the development indicators are quite good and aided by the existence of the application. Therefore, the researcher suggests focusing on socialization and improving the performance of the application.